Enhancing Growth and Yield in Banana Cv. Robusta (AAA) through Fertigation with Microbial Consortium - Senthilkumar, M; Ganesh, S; Srinivas, K; Panneerselvam, P (Journal of Horticultural Sciences, 2013)
Studies were carried out at Indian Institute of Horticultural Research, Bangalore, to test the effect of fertigation with a consortium of biofertilizers for sustainable production in banana cv. Robusta (AAA). The combination of fertigation and consortium of biofertilizers significantly influenced yield and yield-attributing characters in both primary and ratoon crops. Fertigation with 100% recommended dose of fertilizers along with the consortium of biofertilizers recorded significantly higher yield compared to soil application of fertilizer, farm yard manure and consortium of biofertilizers. However, yield difference between 100% and 75% recommended dose of fertilizers was not significant. Likewise, yield difference between 75% and 50% recommended dose of fertilizers (RDF) too did not differ significantly, although yields declined at 50% RDF. Other growth characters such as number of leaves and plant girth were also significantly influenced by the combined application of fertigation and the consortium of biofertilizers in both main and the crops. However, plant height, number of hands per bunch and TSS were not affected by these treatments. Pulp-to-peel ratio significantly differed in both the main plant and ratoon crops, but days to maturity differed significantly in the ratoon crop. Main plant crop yields were higher compared to that in ratoon. N and K accumulation was significantly higher at 100% fertigation with 300g of the consortium of biofertilizers in both the seasons. However, accumulation of phosphorous was higher at 100% fertigation with 300g of the consortium of biofertilizers (CBF) in the plant crop whereas, in the ratoon crop, highest accumulation of P in the stem was observed at 100% RDF+100g CBF, and, in the leaf and fruit, at 100% RDF with 300g and 200g of CBF, respectively.
Keywords: Banana; Drip Irrigation; Fertigation; PGPR; Biofertilizers; VAM